Supporting Molecular Tumor Boards in Molecular-Guided Decision-Making - The Current Status of Five German University Hospitals - Hinderer, Marc; Boerries, Melanie; Haller, Florian; Wagner, Sebastian; Sollfrank, Stefanie; Acker, Till; Prokosch, Hans-Ulrich; Christoph, Jan (Studies in health technology and informatics, 2017)
German university hospitals have started to establish molecular tumor boards in order to enable physicians to make molecular-guided decisions.Our aim was to describe the organizational structure and procedures which are currently supporting the molecular tumor boards of five German university hospitals.We conducted semi-structured interviews with experts of five university hospitals between December 2016 and February 2017.We observed heterogeneity in both the organization of genetic testing and the management of the molecular tumor boards among the five hospitals. They used free-text documents in most of their support procedures rather than machine-readable documents.There are three potentialities to support the process from genetic testing to reporting within the molecular tumor boards: (i) standardized pipeline to integrate automated variant calling and annotation; (ii) tools supporting the experts in creating their reports and presentations and (iii) implementing pharmacogenomic CDSS into clinical routine.
EVALuna2:181
Keywords: Clinical decision-making; Personalized medicine; Pharmacogenetics